Developing team resilience: A season-long study of psychosocial enablers and strategies in a high-level sports team - Morgan, P. B. C.; Fletcher, D.; Sarkar, M. (Psychology of Sport and Exercise, 2019)
Objectives: Previous research exploring team resilience has advanced our definitional, conceptual and theoretical understanding of this construct in elite sport. Although more is known about the psychosocial processes that underpin the resilient characteristics of sports teams, less is known about the contextual enablers that stimulate these mechanisms and the associated pathways to team resilience. The purpose of this study, therefore, is to explore the psychosocial enablers and strategies that promote the development of team resilience within a high-level sport team. Design: and method: Through prolonged fieldwork, a season-long ethnography (11 months) was conducted. The sample consisted of a leading English national league-winning semi-professional rugby union team (n = 27 participants). Multiple data collection methods were employed (i.e., observation, interviewing, field notes, reflexive diary) as part of a holistic ethnographic approach. An iterative process of content data analysis was employed to identify key themes. Results: Findings revealed five categories comprising multiple practical strategies, actions, and enablers for team resilience development: Inspiring, motivating, and challenging team members to achieve performance excellence; developing a team regulatory system based on ownership and responsibility; cultivating a team identity and togetherness based on a selfless culture; exposing the team to challenging training and unexpected/difficult situations; and promoting enjoyment and keeping a positive outlook during stressors. Cultural expressions and folk terms were identified to illuminate the context of the ethnography. Conclusions: This study advanced team resilience research in sport by identifying key psychosocial strategies throughout a season as part of building team resilience. The findings provide practitioners with a platform for creating team resilience interventions in sport.